Persepsi Mahasiwa Tentang Kualitas Pelayanan Kantin Dede Universitas Negeri Padang - Oktarinaldi, Taufik; Kasmita, Kasmita; Suyuthie, Hijriyantomi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aimed to describe students perceptions about the quality of service at Kantin Dede Universitas Negeri Padang,analyzed by five indicators. This type of research is descriptive quantitative research. The population of this research are students who visit the Kantin Dede Universitas Negeri Padang totaling 7250 people. The sampling technique is non-probability sampling, by using incidental sampling. The number of samples in this research amounted to 99 people. Data was collected using a questionnaire with Likert scale that has been tested for validity and reliability. The results showed that: 1) reliability are categorized quite amounting to 49.49%, 2) responsiveness are in good category that is equal to 39.39%, 3) assurance that are in enough category amounting to 53.54%, 4) empathy that are in the category enough that is equal to 49.49%, 5) physical evidence are in good category that is 44.44%.Keywords: Perception, Quality of Service